Disassembly for remanufacturing: A systematic literature review, new model development and future research needs - Anjar Priyono; Winifred Ijomah; Umit S. Bititci (Journal of Industrial Engineering and Management (JIEM), 2016)
Purpose: Disassembly is an important process that distinguishes remanufacturing from conventional manufacturing. It is a unique process that becomes focus of investigation from many scholars. Yet, most scholars investigate disassembly from technical and operational standpoint that lack of strategic perspective. This paper attempts to fill this gap by looking at disassembly from a strategic perspective by considering organisational characteristics, process choices and product attributes. To be more specific, this paper has three objectives. First, to gain understanding what has been done, and what need to be done in the field of disassembly in remanufacturing. Second, to conduct a systematic literature review for identifying the factors affecting disassembly for remanufacturing. Third, to propose a new model of disassembly for remanufacturing and also to provide avenues for future research. Design/methodology/approach: This study used a systematic literature review method. A series of steps were undertaken during the review. The study was started with determining the purpose of the study, selecting appropriate keywords, and reducing the selected papers using a number of criteria. A deeper analysis was carried out on the final paper that meets the criteria for this review. Findings: There are two main findings of this study. First, a list of factors affecting disassembly in remanufacturing is identified. The factors can be categorised into three groups: organisational factors, process choices and product attributes. Second, using factors that have been identified, a new model of disassembly process for remanufacturing is developed. Current studies only consider disassembly as a physical activity to break down products into components. In the new model, disassembly is viewed as a process that converts into into output, which consist of a series of steps. Research limitations/implications: The opportunities for future research include: the need to develop an index of factors affecting disassembly, and how to most appropriate relationship between original equipment manufacturers and contract remanufacturers to share knowledge gained from remanufacturing operations to improve product remanufacturability. Practical implications: Remanufacturers should not focus on product attributes only in order to manage their disassembly process efficiently. Rather, more strategic factors such organisational factors and process choices should also be considered as well. Originality/value: This is the first study that identifies a comprehensive factors affecting disassembly in remanufacturing. In addition, it is for the first time that disassembly is not only viewed as a physical activity, but it is a process that consists of a series of step.
Keywords: 650; remanufacturing; disassembly; sustainability; cores recovery; life cycle analysis; reverse logistics